PENINGKATAN KEMAMPUAN BELAJAR DAN PEMECAHAN MASALAH MELALUI EKSPERIMEN DAN KARYA SAINS ANAK KELOMPOK B PAUD TERPADU ‘AISYIYAH KALIWATES - Mariska Sri Ugita, Putri; Khoiriyah; Dwi Ambarsari, Ferdina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning and problem-solving skills are crucial components of early childhood cognitive development that need to be stimulated through concrete, active, and enjoyable learning experiences. Preliminary observations of Group B at the ‘Aisyiyah Kaliwates Integrated Early Childhood Education Center indicated that the children’s learning and problem-solving skills remain low. The children tend to lack focus, get bored easily, and are not yet able to fully grasp cause-and-effect relationships, as learning is still dominated by the use of magazines and worksheets. This study aims to enhance children’s learning and problem-solving skills through experimental activities and science projects. The study employed a Classroom Action Research approach conducted over two cycles with 15 children aged 5–6 years as research subjects. Data collection techniques included observation, documentation, and assessment of children’s projects, while data analysis utilized quantitative descriptive methods. The results showed an improvement in children’s learning and problem-solving skills in each cycle. In Cycle I, the class average reached 76, falling into the “Developing as Expected” category, and 47% of the children scored above 80. In Cycle II, the improvement was optimal, with the class average reaching 85 and all children (100%) scoring above 80. The children appeared more active, focused, and confident, and were able to understand cause-and-effect relationships through the rainbow water experiment activity, water rockets, Light Up Planets, and Sun Catchers. Research findings indicate that science experiments and science projects are effective learning strategies for enhancing early childhood learning and problem-solving skills through concrete, exploration-based learning experiences.